The Implementation of Smart Box Media on The Learning Outcomes of Social Sciences Students in Grade IV of State Elementary School 31 Lubuklinggau - Putri Melati; Tio Gusti Satria; Sujarwo (Jurnal Profesi Pendidikan, 2025)
This study aims to determine how the learning outcomes of fourth-grade students of SD Negeri 31 Lubuklinggau social studies after the implementation of smart box learning media significantly completed. The research method uses a pre-experimental research method that only involves one class as an experimental class without a control class with a one-group pretest-posttest design, in this design there is a pre-test before treatment and a post-test after treatment so that the conditions after treatment can be compared. The population in this study is fourth grade totaling 42 students. The sampling technique used is a purposive sampling technique, a sampling technique used if the author has certain considerations in sampling or determining samples for certain purposes. Data collection techniques use interview sheets, observation sheets, and written tests. Data analysis techniques use data normality tests and hypothesis tests. The instrument used by the author is in the form of essay questions totaling 10 questions and then after being analyzed, 8 (eight) valid questions are obtained. The data is analyzed using the "t" test. Based on the results of the t-test analysis, t count = 5.08 and ttable 1.73. So tcount (5.08) > ttable (1.72) with this, Ha is accepted and Ho is rejected. Thus, it is concluded that the results of social studies learning of grade IV students of SD Negeri 31 Lubuklinggau after the application